What Next? Islamic State After the ‘Caliphate’ - Quivooij, Romain (2019)
The recapture of territories held by Islamic State (IS) in Iraq and Syria has enticed then Iraqi Prime Minister Haider al-Abadi and US President Donald Trump to proclaim victory over the group. Do such statements reflect on-the-ground realities? How should IS be expected to mutate over the short and long terms?